2020
DOI: 10.1186/s13287-020-01864-8
|View full text |Cite
|
Sign up to set email alerts
|

DNMT1-mediated methylation inhibits microRNA-214-3p and promotes hair follicle stem cell differentiate into adipogenic lineages

Abstract: Background Dysfunction of the DNA methylation was associated with stem cell reprogramming. Moreover, DNA methyltransferase 1 (DNMT1) deficiency was involved in the differentiation of hair follicle stem cell (HFSc), but the molecular mechanisms remain unknown. Methods HFSc from human scalp tissues were isolated and cultured. The oil red O staining was used to observe the adipogenesis. The interaction relationship between microRNA (miR)-214-3p and mitogen-activated protein kinase 1 (MAPK1) was accessed by dual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Ocu-miR-205 can promote hair follicles from the anagen to catagen stage by regulating the expression of genes for proteins in the notch and bone BMP signaling pathways [64]. Other studies showed that miRNA-203, miRNA-214 and miRNA-195-5p express the genes which regulate the development of hair follicles in cashmere goats [65,66] and that MT can influence these miRNAs in the hair follicles of cashmere goats [67,68]. miRNA-211 can regulate the MAPK3 pathway negatively, so it is in keeping with its role in this pathway that MT reduced miR-211 in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Ocu-miR-205 can promote hair follicles from the anagen to catagen stage by regulating the expression of genes for proteins in the notch and bone BMP signaling pathways [64]. Other studies showed that miRNA-203, miRNA-214 and miRNA-195-5p express the genes which regulate the development of hair follicles in cashmere goats [65,66] and that MT can influence these miRNAs in the hair follicles of cashmere goats [67,68]. miRNA-211 can regulate the MAPK3 pathway negatively, so it is in keeping with its role in this pathway that MT reduced miR-211 in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, studies have paid more attention to the function of miR-214-3p modulating stem cell differentiation. 37 , 38 The current study highlights another function of miR-214-3p in rejuvenating aged stem cells, putting forward a potential target for the functional recovery of aged ASCs.…”
Section: Discussionmentioning
confidence: 82%
“…DNMT1 is a key enzyme for DNA to perform replication and repair, and maintain its normal methylation [ 40 ]. DNMT1 is highly expressed in hair follicle stem cells, and DNMT1-mediated miR-214-3p methylation promotes adipogenesis of hair follicle stem cells via MAPK1/p-ERK1/2 axis [ 41 ]. Long noncoding RNA PVT1 inhibits miR-18b-5p expression by recruiting DNMT1, and DNMT1 promotes miR-18b-5p methylation, thereby promoting gallbladder cancer proliferation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%